Developmental effects of antiepileptic drugs and the need for improved regulations - Meador, Kimford J. (Neurology, 2016)
Antiepileptic drugs (AEDs) are among the most common teratogenic drugs prescribed to women of childbearing age. AEDs can induce both anatomical (malformations) and behavioral (cognitive/behavioral deficits) teratogenicity. Only in the last decade have we begun to truly discriminate differential AED developmental effects. Fetal valproate exposure carries a special risk for both anatomical and behavioral teratogenic abnormalities, but the mechanisms and reasons for individual variability are unknown. Intermediate anatomical risks exist for phenobarbital and topiramate. Several AEDs (e.g., lamotrigine and levetiracetam) appear to possess low risks for both anatomical and behavioral teratogenesis. Despite advances in the past decade, our knowledge of the teratogenic risks for most AEDs and the underlying mechanisms remain inadequate. Further, the long-term effects of AEDs in neonates and older children remain uncertain. The pace of progress is slow given the lifelong consequences of diminished developmental outcomes, exposing children unnecessarily to potential adverse effects. It is imperative that new approaches be employed to determine risks more expediently. Our recommendations include a national reporting system for congenital malformations, federal funding of the North American AED Pregnancy Registry, routine meta-analyses of cohort studies to detect teratogenic signals, monitoring of AED prescription practices for women, routine preclinical testing of all new AEDs for neurodevelopmental effects, more specific Food and Drug Administration requirements to establish differential AED cognitive effects in children, and improved funding of basic and clinical research to fully delineate risks and underlying mechanisms for AED-induced anatomical and behavioral teratogenesis.